Let $f: R\to R$, and ($f\circ f\circ f)(x) = (f\circ f)(x) + x$, $x$ $\in \mathbb R.$
Prove that $f$ is injective.

My Solution:

Let $x_1, x_2\in \mathbb R.$ and $f(f(x_1)) = f(f(x_2)) = y$

($f\circ f\circ f)(x) = (f\circ f)(x) + x$

$f((f\circ f)(x)) = f(f(x)) + x$

$f(f(f(x))) = f(f(x)) + x$

$f(f(x)) = f(f(f(x))) - x$

Since $f(f(x_1)) = f(f(x_2))$

$f(f(f(x_1))) - x_1 = f(f(f(x_2))) - x_2$

$f(y) - x_1 = f(y) - x_2$

$-x_1 = -x_2$

$x_1 = x_2$ therefore $f$ is injective.

Is this solution acceptable?


2 Answers 2


You should prove that $f(x_1) = f(x_2)$ implies $x_1 = x_2$. So your solution is not acceptable. You should start with $f(x_1) = f(x_2)$ then say this implies $f(f(x_1)) = f(f(x_2))$ and then complete as you did

  • $\begingroup$ Doesn't $f$ need to be injective in order to say that $f(f(x1)) = f(f(x2))$ if $f(x1) = f(x2)$? $\endgroup$
    – AQUATH
    Aug 4, 2015 at 19:47
  • 1
    $\begingroup$ No, it just needs to be a mapping. $\endgroup$
    – George
    Aug 4, 2015 at 19:48
  • $\begingroup$ Mapping? Googling it comes up with diagrams. (I am not native english speaker therefore I haven't heard the term before). $\endgroup$
    – AQUATH
    Aug 4, 2015 at 19:58
  • $\begingroup$ "mapping" just means that $f$ is essentially a relation between two sets (domain and range). $f:A\rightarrow B$ means that "$f$ maps $A$ to $B$, i.e. that $f$ takes elements in the set $A$ and "pairs" with elements in the set $B$ but isn't necessarily a function. $\endgroup$
    – jdods
    Aug 4, 2015 at 20:18

It looks on the right path if not a bit long: Suppose that $f(x) = f(y)$. Then $$f(f(x)) = f(f(y))\quad \text{and} \quad f(f(f(x))) = f(f(f(y))).$$ Subtract the second equation from the third to get $x=y$.

  • $\begingroup$ Do you (maybe) mean $f(x) = f(y)$? $\endgroup$
    – AQUATH
    Aug 4, 2015 at 19:50
  • $\begingroup$ Oops. I will fix it. $\endgroup$
    – Umberto P.
    Aug 4, 2015 at 19:53
  • $\begingroup$ The $y$ you have set is different than mine, isn't it? Cause otherwise you would get $f(x) = f(f(f(x)))$ $\endgroup$
    – AQUATH
    Aug 4, 2015 at 19:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.